ONOMASTICS AS A LINGUISTIC DISCIPLINE AND ITS NINE STRUCTURAL SUBFIELDS - Abdubannonova Mavluda; Xakimbayeva Ozoda Kalandarovna (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article explores the field of onomastics, detailing its nine subdivisions and their significance in understanding names and naming practices. It examines etymology, anthroponymy, toponymy, and more, providing a comprehensive overview of how names shape cultural identity and social structures.